Advancing Equity in Faculty Hiring with Diversity Statements. (25th January 2022) - Bombaci, Sara P; Pejchar, Liba
Abstract: Hiring diverse candidates and creating an inclusive and equitable climate has emerged as a top priority for the scientific community. Diversity statements are a common but unexamined tool for recruiting a more diverse workforce. We surveyed more than 200 experts in diversity, equity, and inclusion (DEI) from US academic institutions to synthesize strengths and limitations of diversity statements and to develop guidelines for using such statements in faculty hiring. We found overwhelming agreement that diversity statements are a valuable tool for the advantages they offer the institution and applicant, but the experts indicated that diversity statements should be supported by other evidence. We further found that few institutions provide guidance on how to effectively use diversity statements in the hiring process. We address this need by providing an expert-derived evaluation framework for recognizing and rewarding DEI in the recruitment process that can be flexibly adapted to fit the unique requirements of diverse institutions and positions.